A Prospective Study to Monitor for Tuberculosis During Anti-tumour Necrosis Factor Therapy in Patients With Inflammatory Bowel Disease and Immune-mediated Inflammatory Diseases. (11th May 2018) - Lee, Choon Kin; Wong, Sunny H v; Lui, Grace; Tang, Whitney; Tam, Lai San; Ip, Margaret; Hung, Esther; Chen, Minhu; Wu, Justin C; Ng, Siew C
Abstract: Background: Biologic therapies have revolutionised the treatment of immune-mediated diseases including inflammatory bowel disease [IBD] and rheumatological disorders. However, biologic treatments are associated with an increased risk of reactivation of latent tuberculosis. Data from regular monitoring for latent tuberculosis infection [LTBI] during biologic treatment are lacking. Methods: Consecutive patients eligible for biologic therapies were screened for LTBI and prospectively followed up for 3 years. Incidence and risk factors of latent tuberculosis tests conversion (interferon gamma release assays [IGRA], tuberculin skin tests [TST], and chest radiography [CXR]) with clinical outcomes were studied. Results: A total of 108 patients [83 IBD; 25 rheumatological disorders] were included. At baseline, 18/108 [16.7%] patients [five IBD; 13 rheumatological disorders] were tested positive for LTBI. Of these, 14/18 [77.8%] patients received isoniazid monotherapy for 9 months. Of the remainder, 17/90 [18.9%] patients had LTBI test conversion while on biologic therapies and of these 14/17 [82.4%] received isoniazid monotherapy for 9 months. Age, sex, smoking status, alcohol use, travel history, disease type, and immunosuppressive therapy were not associated with LTBI test conversion. In subjects with IGRA conversion, serial IGRA levels normalised after completion of isoniazid except in one patient whose IGRA remained persistently elevated despite isoniazid and who subsequently developed active TB. Conclusions: Conversion of LTBI is common and occurred early during biologic therapy in an area with intermediate TB burden. Subjects with latent TB tests conversion and persistently high IGRA levels may have an increased risk of TB reactivation or development of active TB, and they require close observation or intensive workup for active TB.